P37. Effects of acetyl-dl-leucine on the cerebral activation pattern in cerebellar ataxia (FDG-PET study). Issue 8 (August 2015) - Becker-Bense, S.; Feuerecker, R.; Xiong, G.; Feil, K.; Bartenstein, P.; Strupp, M.; Dieterich, M.
<x xml:space="preserve">Abstract</x> Introduction A recent case series study showed significant improvements of symptoms in patients with cerebellar ataxia on medication with the amino acid acetyl-dl-leucine (Tanganil) (Strupp et al., 2013). In analogy to electrophysiological studies in animals it was hypothesized that acetyl-DL-leucine modulates the activity of central vestibular neurons, preferably in the cerebellum, by normalizing the membrane potential of depolarized or hyperpolarized neurons and thereby improves central compensation. However, the mode of action of acetyl-dl-leucine and the site of central compensation remained speculative. To deepen our insights in the central compensatory processes induced by acetyl-dl-leucine we performed a FDG-PET study in cerebellar ataxic patients off and on treatment. Methods 21 patients with cerebellar ataxia of different etiologies were scanned by resting state FDG-PET twice, (A) off treatment (PET 1), and a second time (B) ⩾3 months on treatment with 5g/day acetyl-dl-leucine (PET 2; n = 18). At both time points the patients underwent a detailed neurological examination and measurements of standardized ataxia scales (SARA, SCAFI). Group subtraction analyses (PET 1 vs. PET 2; responders vs. non-responders) as well as statistical group comparisons with age- and gender-matched healthy controls were calculated with statistical parametric mapping (SPM). Results The contrast on vs. off treatment (PET 2 vs. PET 1) mainly showed signal differences in the mesencephalon (midbrain integration centers) as well as in the lateral medullary brainstem (vestibular nucleus region), thalami and midinsular regions bilaterally. The contrast PET 1 vs. PET 2 revealed signal differences in the posterior insula as well as in primary and secondary visual areas (including MT/V5) bilaterally. Restricting the analyses to treatment-responders (n = 11), PET 2 vs. PET 1 showed similar signal areas in the central midbrain and dorsal medullary brainstem bilaterally that were lacking in the corresponding contrast of the non-responders (n = 6). In the direct comparison of responders vs. non-responders PET 2 signal differences were located in both caudate nuclei, the superior temporal gyrus and hippocampus. The signal in responders – mainly in the posterior insula and the medial temporal gyrus – was lower compared to non-responders. In all contrasts cerebellar signal changes were sparse. Conclusions Central compensatory processes induced by acetyl-dl-leucine in cerebellar ataxia seem to involve mainly centers in the medulla (vestibular nuclei), midbrain (vestibular integration centers), thalami, basal ganglia and insular regions rather than neurons in the cerebellum, the primary site of dysfunction in cerebellar ataxia syndromes.